THE NEXUS OF POWER AND OPPRESSION: A FOUCAULDIAN AND GRAMSCIAN STUDY OF PROSPERO’S DOMINANCE IN THE TEMPEST - Marfu'ah, Elsa Lailatul; Saputra, Arya; Wicaksono, Tito Aryo; Kusniah, Mariam; Nurjanah, Hidayatul (Elite : English and Literature Journal, 2023)
This study focuses on the intricate power dynamics and hegemonic structures in William Shakespeare’s The Tempest, focusing on Prospero’s dominion over his subordinated subjects, Ariel and Caliban. Drawing from Michel Foucault’s power relations and Antonio Gramsci’s hegemony, the study reveals that power within the narrative transcends physical coercion, encompassing the manipulation of cultural, political, and ideological elements. The findings unveil the complex interplay of forces governing authority, subjugation, and the imposition of cultural and intellectual control in the context of the master-slave relationship. Prospero, as the master, employs language and narrative manipulation to assert his dominance over Ariel and Caliban, yielding both physical and psychological control. The themes of oppression and colonialism within the play are distinctly portrayed, notably through the enslavement of Caliban and Ariel, emphasizing their resilience against prevailing power imbalances. Moreover, this research extends beyond Shakespeare’s work, functioning as a metaphor for contemporary societal challenges related to power, dominion, and resistance. Ultimately, the interplay of power and oppression within The Tempest provides a profound lens through which to examine the intricacies of power within the broader spectrum of human existence, enriching our understanding of power dynamics in literature and their significance in contemporary societal issues.